2004
DOI: 10.1002/crat.200310223
|View full text |Cite
|
Sign up to set email alerts
|

On the effects of Ga3+ and La3+ ions in MgCu ferrite: Humidity‐sensitive electrical conduction

Abstract: Pure and gallium or lanthanum substituted MgCu ferrites, Mg 0.5 Cu 0.5 Fe 2-x M x O 4 (with x = 0 or 0.2 and M = La or Ga) have been prepared by solid state reaction. Sintering experiments were carried out at different temperatures between 900 and 1100°C. The phase composition and lattice parameters were determined by XRD, while the effect of Ga and La substitutions on the granular structure was studied by SEM. Experimental results revealed that the densification behaviour and some physical properties are in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Samy [18] has studied magnetic and electrical properties of R = La, Nd, Sm, Gd substituted Cu-Zn ferrite and reported decrease in saturation magnetization and grain size. An increase in resistivity and porosity of La 3+ substituted Mg-Cu ferrite has been reported by Rezlescu et al [19] and further they showed that conduction in ferrite is sensitive to microstructure. Roy et al [20,21] have studied the magnetization measurements of La 3+ substituted Ni-Cu-Zn ferrite using different techniques and reported an increase in saturation magnetization, resistivity and permeability.…”
Section: Introductionmentioning
confidence: 85%
“…Samy [18] has studied magnetic and electrical properties of R = La, Nd, Sm, Gd substituted Cu-Zn ferrite and reported decrease in saturation magnetization and grain size. An increase in resistivity and porosity of La 3+ substituted Mg-Cu ferrite has been reported by Rezlescu et al [19] and further they showed that conduction in ferrite is sensitive to microstructure. Roy et al [20,21] have studied the magnetization measurements of La 3+ substituted Ni-Cu-Zn ferrite using different techniques and reported an increase in saturation magnetization, resistivity and permeability.…”
Section: Introductionmentioning
confidence: 85%
“…The particles are lumped and become compact. The SEM image of magnesium ferrite indicated that the distribution of grain size obtained by this process is smaller than that obtained through the ceramic route [20,21]. Aggregation of smaller grains was observed with the formation of lesser pores.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Rezlescu et al [7] reported the influence of Ga 3 þ and La 3 þ in Mg-Cu ferrites. A systematic study of the dielectric properties of Mg-Zn ferrites as a function of frequency and composition has been reported by Mansour [8].…”
Section: Introductionmentioning
confidence: 98%